Judicial Ethics: A Key Tenet to Legal Ethics - Achode, Lydia (Strathmore Law Journal, 2022)
Judicial ethics are arguably one of the most important aspects of legal ethics Values of legal ethics such as decorum, dignity, courtesy, and rationality that were emphasized by the late but still foremost scholar of professional legal ethics, Deborah Rhode, readily apply to the judicial context.. Related to these values, judicial ethics ensures that three important attributes or three ‘Is’ characterise the judicial process and the conduct of judicial officers: independence, impartiality and integrity. Adherence to these three principles of judicial ethics is key in securing the administration of justice, professional discipline in the judiciary, and public confidence. This article therefore takes the view that the competence of judges not only includes their academic qualifications but their possession of qualities necessary to fulfil the three Is and other standards of ethical judicial conduct. Moving from this understanding, the article analyses how judicial ethics, as a derivation of legal ethics, shapes the role of judges and, further, how Kenya’s Judicial Service (Code of Conduct and Ethics) Regulations integrates established principles of judicial ethics. From this analysis, the author argues that judicial ethics are inseparable from judicial competence and that Kenya’s Judicial Service (Code of Conduct and Ethics) Regulations effectively reflect the necessary principles of judicial ethics. Thus, continued enforcement of the judicial Code of Conduct and Ethics is essential to safeguarding judicial ethics in the Kenyan judiciary.